Penguatan Kinerja melalui Pelatihan Pengelolaan SDM pada Karang Taruna Kelurahan Krobokan - Kusumawati, Diah Ayu; Nugrahini, Dian Essa; Purnamasari, Verina (Penerbit Goodwood, 2025)
Purpose: This activity aims to provide training on the human resource management system (HR) in Karang Taruna to optimize the performance of its organization. Methodology/approach: The community service team conducted training and mentoring in the preparation of the HR management system through job design which includes job specifications, job descriptions and organizational structure. Furthermore, the team conducted monitoring and evaluation to see to what extent the job design was maximally implied in the Karang Taruna organization. Results/findings: The results of this community service activity are that Karang Taruna has an organizational structure, but does not yet have a detailed job design including job specifications and job descriptions. In its organizational activities, the Karang Taruna management does not make maximum use of the abilities of its members and there is a lack of clarity in the job description. So this results in the less than optimal performance of the Karang Taruna organization. Conclusions: This activity increased the Karang Taruna Krobokan administrators’ understanding of HR management from 52.2% to 87.3% and encouraged the implementation of a more structured HR system to optimize organizational performance. Limitation: The limitation of this community service activity is the limited time in analyzing and understanding the condition of the youth organization so that in the job design process, there is less detail in terms of job specifications, job descriptions and organizational structure. Contribution: Training and mentoring in the preparation of the HR management system in this community service activity is able to optimize the performance of the youth organization through the application of the organizational design.